CLINICAL AND DIAGNOSTIC FEATURES OF ENDOMETRIAL HYPERPLASTIC PROCESSES IN POSTMENOPAUSAL WOMEN - Garashova, M.A.; Alieva, E.M.; Mammadova, L.D. (World of Medicine and Biology, 2021)
The study included data from 65 patients with endometrial hyperplasia in the postmenopausal period, of which 56 (86.2 %) had spotting, 32 (49.2 %) had sleep disorders, 29 (44.6 %) had emotional lability, 21 (32.3 %) had dysuric phenomena, 20 (30.8 %) had pain of varying intensity, 15 (23.1 %) had rapid fatigue, and 7 (10.0 %) had bleeding. Studies have found that 85.5 % of women had a history of high birth rates, of which 100 % of women had artificial abortions. The frequency of infertility in this group of patients was 5.2 %. 12 (18.5 %) patients had episodes of recurrent endometrial hyperplasia in the reproductive period. The data of the transvaginal echography showed that the most specific echographic indicator in postmenopausal endometrial hyperplasia is an increase in the thickness of the endometrium, ranging from 14.1±1.6 mm in patients with atypical endometrial hyperplasia to 21.3±4.8 in patients with diffuse endometrial hyperplasia. The study of the parameters of CA 125 revealed its significant fluctuations, which proved the lack of diagnostic significance in this pathology.